AN ASSESSMENT OF REGIONAL SOCIO-ECONOMIC PROJECTS - Vadim A. Lomazov; Viktoria S. Nehotina (Статистика и экономика, 2016)
The problem of development of models and methods for carrying out the assessment of socio-economic projects is examined. The approach to informational simulation of project status on the basis of the determined, statistical and linguistic description of separate indexes is offered. A hierarchical procedure of calculation of project’s resulting figure is developed.